The Relationship of Spirituality and Resilience in Patients that Received Hemodialysis - Dila Novita; Cucu Rokayah; Rizky Muliani; Sumbara Sumbara (GLOBAL HEALTH SCIENCE GROUP, 2022)
Patients undergoing hemodialysis result in physical and psychological problems. Psychological problems can cause a decrease in the resilience of hemodialysis patients, resulting in delays in the healing process, so spirituality is needed to help overcome the problem. The purpose of this study was to determine the relationship between spirituality and resilience in patients undergoing hemodialysis at Al-Ihsan Hospital, Bandung Regency. This type of research is quantitative research with correlational methods. Research instrument with Spiritual Well-Being Scale (SWBS) and Connor and Davidson Resilience Scale (CD-RISC). The study population was 180 patients with a sample of 125 hemodialysis patients, using purposive sampling technique. Data analysis with univariate and bivariate using Spearman rank correlation test. The results of the study of high spirituality (90.4%), low resilience (51.2 %), the relationship between spirituality and resilience (ρ) = 0.022. Based on the results of the study, there was a significant relationship between spirituality and resilience in patients undergoing hemodialysis at Al-Ihsan Hospital, Bandung Regency. It is hoped that further researchers can examine other resilience factors in patients undergoing hemodialysis.